Pemotongan Daun Worm Screw Setengah Lingkaran Untuk Mengurangi Broken Nut Pada Statiun Press PT X - Armanda Purba (CV MEDAN TEKNO SOLUSI, 2023)
The worm screw press is one of the main components of the Crude Palm Oil extracting machine. The purpose of this research is to find out the amount of pressure that acts on the worm screw press when pressing fiber and nuts. Where in this study there has been a change in the dimensions of the worm screw by cutting the semicircular leaves to get the percentage of broken nuts produced. The research took place from visual inspection and factory testing including tool testing, pressure, and studying the process, the working principle of the screw press machine and recording the specifications of the screw press tool. From the test results, it was found that the worm screw press pressure before cutting was 10676.17 N.m2, while the worm screw press pressure that occurred after cutting the semicircular leaves was 9857.05 N.m2. The greater the worm screw press pressure that works to get maximum oil pressing results but causes broken nuts to be included in the dregs of the press, while the small worm screw press pressure causes oil losses but produces a few broken nuts. The disturbance that occurs in the screw press is a pressure problem.